2004
DOI: 10.2355/isijinternational.44.1945
|View full text |Cite
|
Sign up to set email alerts
|

Development of High Strength Hot-rolled Sheet Steel Consisting of Ferrite and Nanometer-sized Carbides

Abstract: A ferritic steel precipitation-strengthened by nanometer-sized carbides was developed to obtain a high strength hot-rolled sheet steel having tensile strength of 780 MPa grade with excellent stretch flange formability.Manganese in a content of 1.5 % and molybdenum in a content of 0.2 % were added to 0.04 % carbon Tibearing steel in order to lower austenite-ferrite transformation temperature for fine carbides and to retard generating of pearlite and large cementites, respectively. Tensile strength of hot-rolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
291
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 469 publications
(299 citation statements)
references
References 1 publication
8
291
0
Order By: Relevance
“…These precipitates are NaCl-type FCC structured alloy carbides. In the Ti-added steel the carbides are TiC with an atomic ratio of Ti and C of approximately 1:1, while in the Ti,Mo-added steel the carbides are (Ti,Mo)C, 17,18,25,26) where some of Ti atoms in TiC carbides are replaced by Mo atoms. The spacing of such particle sheets was approximately 25 nm and 20 nm in the Ti-added and Ti,Mo-added steels, respectively, i.e.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
See 1 more Smart Citation
“…These precipitates are NaCl-type FCC structured alloy carbides. In the Ti-added steel the carbides are TiC with an atomic ratio of Ti and C of approximately 1:1, while in the Ti,Mo-added steel the carbides are (Ti,Mo)C, 17,18,25,26) where some of Ti atoms in TiC carbides are replaced by Mo atoms. The spacing of such particle sheets was approximately 25 nm and 20 nm in the Ti-added and Ti,Mo-added steels, respectively, i.e.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…It has been reported that ferritic steels with nano-sized alloy carbides produced by interphase precipitation show both very high strength and good formability, and some kinds of alloy steels have already been in commercial use. [13][14][15][16] Many studies have been reported on mechanical properties of interphase precipitated steels so far, [17][18][19][20][21][22][23] but effects of nano-sized alloy carbides by interphase precipitation on strength and ductility of materials are not yet clear. In the present study, ferrite single phase steels with nano-sized alloy carbides were prepared using Ti,Mo-added low carbon steels, and tensile behavior of the samples were systematically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The steel industry has responded to this challenge by developing single-phase ferritic steels strengthened by interphase precipitation based on various micro-alloying systems. [3][4][5][6] Interphase precipitation consists of periodic rows of carbide precipitates which form simultaneously with the decomposition of austenite and growth of ferrite. 7) The periodicity of these carbide precipitate rows and spacing of precipitates on each respective row strongly influences the mechanical properties through the Ashby-Orowan mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important technique to inhibit softening of the heat-affected zone during welding [3]. Other important roles of precipitates include improvements of hole expandability [4] and the hydrogen trap to prohibit the hydrogen embrittlement [5,6].…”
Section: Introductionmentioning
confidence: 99%